STUDY OF THE MOVING AVERAGE METHOD'S APPLICATION IN REDUCING POWER FLUCTUATIONS IN HYBRID GENERATION SYSTEMS FOR ISOLATED AREAS - Ismail, Syaiful
Hybrid generation systems that integrate solar power plants are becoming an important element in the drive toward more sustainable energy sources. While it has great potential to reduce dependence on fossil fuels and address climate change, the main challenge faced is power fluctuations stemming from the intermittent nature of sunlight as the main energy source of solar power plants. These fluctuations create uncertainty in energy production and are a challenge for hybrid generation systems in maintaining a stable electricity supply. The purpose of this research is to examine the application of the moving average method as a solution to overcome the problem of power fluctuations in a hybrid generation system consisting of two types of renewable energy sources, namely solar and micro-hydro power plants, and to utilize the battery system as the main component in the application of the moving average method. The solar power plant system consists of PV modules connected to the DC bus through a boost converter as well as a battery system connected through a bidirectional DC/DC Buck-Boost converter. The moving average method is applied specifically to the battery system, which absorbs and releases power to balance the PV power output. The process of absorbing and releasing battery power is based on the power reference generated from the Moving Average Method. The relationship between the actual PV power and battery power will produce smoothing power, which will then be supplied to the main AC system network through a DC-AC converter connected to the AC bus integrated with the micro-hydro power plants system and loads. In this research, the simulation is carried out using MATLAB/Simulink and focuses on the actual PV power, battery power, and smoothing power.